Replicating a seventeenth century sword - Giovanni Sartori (Bern Open Publishing, 2019)
Making a good "copy" of an ancient weapon means to reach different targets, not only regarding the final product of the making process but also the process itself. This means that to make a sword like this, it is necessary to initially study all the material regarding swords and blades from the same period and geographic area. This process involves not only their style, design, geometry, weights and balance, but also the cultural background of the period, the use and symbolism of the weapon and finally the original production techniques used. This article reviews and documents the "Storta project" in the context of a museum exhibition in Minsk (European Martial Arts: From Vulcan's Forge to the Arts of Mars, 01.05-30.09.2019).